Obesity and Aging - Malandrino, Noemi; Bhat, Salman Z; Alfaraidhy, Maha; Grewal, Rajvarun S; Kalyani, Rita Rastogi (Endocrinology and metabolism clinics of North America, 2023)
The obesity epidemic in aging populations poses significant public health concerns for greater morbidity and mortality risk. Age-related increased adiposity is multifactorial and often associated with reduced lean body mass. The criteria used to define obesity by body mass index in younger adults may not appropriately reflect age-related body composition changes. No consensus has been reached on the definition of sarcopenic obesity in older adults. Lifestyle interventions are generally recommended as initial therapy; however, these approaches have limitations in older adults. Similar benefits in older compared with younger adults are reported with pharmacotherapy, however, large randomized clinical trials in geriatric populations are lacking.